Digestion and ruminal fermentation of cocoa pod silage based ration enriched by gliricidia and calliandra leaves on goats - Puastuti W; Widiawati Y; Wina E (Indonesian Center for Animal Research and Development (ICARD), 2015)
In term of availability, cacao pod is potential for ruminant feed. According to its nutrients content, cacao pod can be used as feed fiber source. Protein sources materials must be added when cacao pod was ensilaged due to low protein content of this material. The aim of this study was to investigate digestibility value and end products of rumen fermentation of goat fed grass or cacao pod based ration. Randomized block design and 20 heads of lambs (16.95±2.36 kg) to evaluated 5 type of rations: R (50% grass + 50% concentrate); S (50% cacao pod silage + 50% concentrate); SG (50% cacao pod-gliricidia silage + 50% concentrate); SK (50% cacao pod-calliandra silage + 50% concentrate) dan SC (50% cacao pod-mixture of gliricidia-calliandra silage + 50% concentrate). Feeding trial was conducted for over 15 weeks. Measurements were taken on feed digestibility and rumen-fermentation end-products after 3 weeks of treatments. Results shows that nutrients digestibility was different significantly among the groups of treatments (P<0.05). Digestibillity of organic matter, NDF and energy of R ration was those of higher significantly (P<0.05) than those of other groups. N-ammonia of rumen from goat feed R ration was higher (P<0.05) than other groups. Total VFA and each component were different among the groups (P<0.05), however the value was similar among the groups of cacao pod silage rations. It is concluded that cacao pod silaged based rations enriched by Gliricidia and Calliandra leaves did not produce similar digestibility value and end products of rumen fermentation with grass based ration.